ANALISIS KINERJA ORGANISASI BADAN PELAYANAN PERIJINAN TERPADU KOTA SEMARANG (Studi Kasus pada Bidang Perijinan Kesejahteraan Rakyat dan Lingkungan) - Mona Agisa Widia Gutama; Hesti Lestari; Sundarso Sundarso; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The success a government can be seen from quality of public service received by society. The level of public service depend on performance of birocracy as public service administrator. Integrated Licensing Service Agency is a public organization providing one stop service. The purpose this study is to perceive performance Semarang of Integrated Licensing Service Agency performance and to know supporting and restricting factor focused on Licensing Public Welfare and Environment department. Evaluation this study based five dimension including productivity, service quality orientation, responsiveness, responsibility and accountability, while supporting and inhibiting factors seen from human resources, infrastructure, management information system and work culture. This research approach is qualitative descriptive labels using informant from Semarang of Integrated Licensing Service Agency and public service users. The study result of Licensing Public Welfare and Environment showed its performance is not optimal, because researcher found problems in productivity, service quality orientation, responsiveness and responsibility. Researcher also found that limited human resources, infrastructure and work culture are the restricting factor of public service implementation. According this study, researcher reccomend some suggestions can be done by Semarang of Integrated Licensing Service Agency to incease their performance, creating coordination and good cooperation with technical team, setting public service survey as standard performance assesment, increasing socialization and sensitivity in socienty need and making sistematic procedure of licensing requirement. As for the review of the restricting factors need to improve the quality and quantity of human resources, improve infrastructure and determine target the completion of licensing per day.